Effectiveness of Jigsaw Type II Cooperative Learning Model in Improving Self-Efficacy, Activities, and Learning Outcomes of STKIP Pembangunan Indonesia Makassar Students - Sari, Nur Indah; Ahmad, Fandi (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The main purpose of this study was to determine whether the Jigsaw II Cooperative learning model was effective in increasing the self-efficacy of Indonesian Development STKIP students, in the Learning Assessment course. This research is a quasi-experimental research. The population in this study were all students of Biology Education Study Program Semester IV (four) academic year 2020/2021 Even Semester STKIP Indonesian Development Makassar. The samples used are two classes that have the same initial ability, namely classes IVA and IVC. The reason for choosing the IVA class as the control class and the IVC class as the experiment. The data collection technique in this study used a pretest-posttest control group design model. Data analysis was carried out using description analysis, N-Gain test, prerequisite test and hypothesis testing with the help of SPSS 17. Based on the test results, it was found that the application of the Jigsaw Cooperative Learning Model Type II was quite effective in increasing self-efficacy with the percentage of Ngain 61%, student learning activities of 90% which means very effective and learning outcomes obtained by the percentage of Ngain 56% which means quite effective.